👤

radical din 3 ( radical din 27+4 radical din 3

Răspuns :

[tex]\sqrt{3}*(\sqrt{27}+4\sqrt{3})=\sqrt{3}*(\sqrt{9*3}+4\sqrt{3})=\sqrt{3}*(\sqrt{9}\sqrt{3}+4\sqrt{3})=\\ \sqrt{3}*(\sqrt{3*3}\sqrt{3}+4\sqrt{3})=\sqrt{3}*(3\sqrt{3}+4\sqrt{3})=\sqrt{3}*[(3+4)\sqrt{3}]=\\ \sqrt{3}*(7\sqrt{3})=\sqrt{3}*(\sqrt{7^{2}*3})=\sqrt{3}*(\sqrt{49*3})=\sqrt{3}*(\sqrt{147})=\\ \sqrt{3*147}=\sqrt{441}=\sqrt{21*21}=21[/tex]
[tex] \sqrt{3} ( \sqrt{27} +4 \sqrt{3} )= \sqrt{3} (3 \sqrt{3} +4 \sqrt{3} )= \sqrt{3} \cdot 7 \sqrt{3} =7 \cdot 3=21[/tex]